Factors Affecting Control Room Operator Situation Awareness and ITS Fuzzy Logic Model - Asep Karmana; Fergyanto E. Gunawan; Muhammad Asrol (Publikasi Indonesia, 2024)
The rapid development of computer-human interface in process industries control systems challenged control room operator (CRO) to maintain their situation awareness (SA) at the high alert level. The paper aims to present physiological factors affecting the work performance of CRO wellness status during their duty to measure their SA level. PERCLOS number of eye-opening recognition and heart rate profile used as physiological variable to measure fatigue effect. Alarm management records and response time spent in controlling process changes behavior used as cognitive behavior variable representing competency performance. Fuzzy logic methods selected to correlate the input variables to the SA level as output variable that will be useful to communicate the CRO situation awareness status into the computer human interface as an alert system for the CRO themselves or further to their supervisor for any intervention required. Results of the observation and analysis shows a significant correlation between the observed physiological of the CRO and the cognitive behaviour of the CRO at different stress level working condition. The findings support the development of wellness alert system in process industries control system through enhancing SA level of CRO effectively.